Muhammad Arsyad Al-Banjari sebagai Ulama Nusantara: Kajian Metodologi Sejarah terhadap Karya Arsyad Al-Banjari - Firmansyah, Siddik (IAIN Syekh Nurjati Cirebon, 2024)
Â Intellectual Sheikh Muhammad Arsyad al-Banjari was a Nusantara Ulama who was very influential in the spread of Islamic da'wah in his homeland in Banjar. Muhammad Arsyad Al-Banjari in spreading Islam had a great influence on the people of Banjar. He was the beginning of the leading scholars who gave birth to the scholars of the next generation in da'wah. The purpose of this research is to show that Arsyad al-Banjari also has a broad quality of knowledge, and some of his works are still largely invisible. Qualitative research method with descriptive analysis. The results of Arsyad al-Banjari's research besides the well-known scholars in Banjar in the science of fiqh who rely on his work Sabil al-Muhtadin is also an expert in the science of Sufism, Akidah, and an expert in the science of hadith, the science of hadith can be found in the fiqh works of Sabi al-Muhtadin and The creed of Tuhfah al-Raghibin. Although his work has not been specifically found in the science of hadith, the traditions contained in these two works prove that the knowledge of hadith possessed by Arsyad al-Banjari is extraordinary, then he makes water irrigation, establishes a new village, establishes a court of Islamic law and preaches. . Al-Banjari is a well-known cleric who spread Islam more broadly with shari'ah, creed, and Sufism based on Ahl Sunnah wa al-Jamaah with the Shafi'i school of thought in Banjar, South Kalimantan.